2019
DOI: 10.4103/tjo.tjo_56_19
|View full text |Cite
|
Sign up to set email alerts
|

Role of tear film biomarkers in the diagnosis and management of dry eye disease

Abstract: In recent years, there has been increasing scientific interest in the use of tear film biomarkers in the diagnosis and management of dry eye disease (DED), owing to their potential important roles in the pathogenesis of ocular surface damage, as well as the technical feasibility of tear sample collection techniques. An Entrez PubMed search was conducted on March 2, 2019, to include papers investigating the use of tear film biomarkers in DED, and the results were classified according to whether the DED is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 54 publications
(244 reference statements)
0
10
0
Order By: Relevance
“…Various authors have studied the influence of DED on the presence of different inflammation markers at ocular level. It has been reported that there is a significant increase of inflammation, doubling the concentration of IL-8 in patients with DED compared with healthy controls [ 2 , 81 ]. This high concentration of IL-8 at the tear level leads to the migration of different immune cells towards the eye, triggering the aggravation of the ocular inflammation symptoms present in the disease [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various authors have studied the influence of DED on the presence of different inflammation markers at ocular level. It has been reported that there is a significant increase of inflammation, doubling the concentration of IL-8 in patients with DED compared with healthy controls [ 2 , 81 ]. This high concentration of IL-8 at the tear level leads to the migration of different immune cells towards the eye, triggering the aggravation of the ocular inflammation symptoms present in the disease [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…While tears are available in considerably reduced volumes for sampling, they are a neglected key reservoir of biomarkers, with great potential in medical diagnostics [179,180]. Tears are complex protein, lipid, mucin, water and salt mixtures, and the development of novel proteomic, lipidomic and glycomic techniques has allowed for a complete understanding of these components and their changes associated with ocular or non-ocular disorders [171,181,182]. For example, proteomic techniques have revealed the presence of AD-related peptides within aqueous humor samples [183], while tear fluid has proven to be clinically relevant through the discovery of a combination of four tear proteins, namely lipocalin-1, dermicidin, lysozyme C and lactritin, with a sensitivity of 81% and a specificity of 77% for AD [184,185].…”
Section: Emerging Body Fluid Biomarkersmentioning
confidence: 99%
“…Tear samples were analyzed for pro-inflammatory cytokines IFN, IL-6, IL-8, by means of ELISA using a Luminex multiplex basis (which enables the quantification of the three proteins simultaneously in the same sample). 20 Lipid expression was evaluated by mass spectrometry. Four molecules were studied: ceramides, sphingomieline, sphingosine and sphingosine 1 phosphate.…”
Section: Cytokine and Lipid Analysismentioning
confidence: 99%